2020
DOI: 10.1002/fam.2891
|View full text |Cite
|
Sign up to set email alerts
|

A Round Robin of fire modelling for performance‐based design

Abstract: Summary Nine participants, representing eight different Swedish fire consultancy firms participated in a Round Robin study where two different cases were simulated with the Fire Dynamics Simulator. The first case included a large open warehouse where the activation of a sprinkler system was to be studied. In the second case time to critical conditions in a theatre was to be calculated. The participants were given clear instructions on the building layout and heat release rate for the two cases. Still, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Modeling these fires requires capturing large-scale atmospheric conditions and flows over large regions as well as the small-scale details of flame fronts. This is driving the development of a number of items: better support for massively parallel computations, 1 The characteristic fire diameter is related to the characteristic fire size via the relation…”
Section: Future For Enclosure Fire Field Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling these fires requires capturing large-scale atmospheric conditions and flows over large regions as well as the small-scale details of flame fronts. This is driving the development of a number of items: better support for massively parallel computations, 1 The characteristic fire diameter is related to the characteristic fire size via the relation…”
Section: Future For Enclosure Fire Field Modelmentioning
confidence: 99%
“…Several so-called "Round Robin" studies have been conducted where a number of professionals in research or engineering are asked to use a model to simulate a given experimental setup or an enclosure fire scenario, and their simulation results are compared. Such studies have shown that there can be a considerable discrepancy in the results depending on the user and the user's assumptions made on various input data [1].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we invited six volunteer participants who have different levels of knowledge and experience from different fire engineering companies or research institutes. Similar round-robin approach and group efforts were adopted in simulating the Dalmarnock Fire Test One [69][70][71], warehouse and theatre [72]. Each participant is asked to evaluate the ASET of two atrium cases, as if it is a normal consultancy task or research project.…”
Section: A Round Robin Of Conventional Pbd By Human Professionalsmentioning
confidence: 99%
“…The evacuation route is also affected by the conditions of fire development in the surroundings [5,6]. Additional elements are the issues related to fire resistance of building structures and their components [7][8][9]. The design of fire protection systems in underground objects is a complex, multi-stage issue, which creates many problems for designers [10,11].…”
Section: Introductionmentioning
confidence: 99%